Vibracores collected in Quarantine Bay, Louisiana, United States of America - Alexander Kolker; Dallon Weathers; Swann Christy; Renfro Alisha (PANGAEA, 2025)
This dataset contains vibracore samples collected in Quarantine Bay, located in southeastern Louisiana, USA, on the east side of the lower Mississippi River. Sampling was conducted on 12 and 13 June 2023. The primary objective was to investigate the geology of Quarantine Bay, which serves as the receiving basin for Neptune Pass—the largest new distributary of the Mississippi River. Sediment cores were collected using a vibracorer, a standard technique employed in the Mississippi River Delta and other coastal environments. The coring apparatus utilized aluminum pipes with a diameter of 7.6 cm. Core compaction was assessed during collection by comparing the depth of sediment recovered in the barrel to water depth measurements taken via tape measure and/or hand ruler. The spatial extent of the study area ranges from 29.432624°N to 29.375139°N latitude and from -89.522453°W to -89.458961°W longitude. Specific core locations are provided in the associated data table.